Pengaruh likuiditas, kualitas aset, sensitivitas pasar, dan efisiensi terhadap Return On Asset (ROA) pada bank devisa yang go public - Rommy Rifky Romadloni; Herizon Herizon (Journal of Business & Banking, 2015)
Banks are the financial institutions that have functions as the intermediary between the two parties such as those who need capital and those who have excessive capital. This research aims to analyze whether LDR, LAR, IPR, NPL, APB, IRR, PDN, BO-PO, and FBIR simultaneously and partially have significant effect on ROA. It uses secondary data taken by means of documentation method. These data were taken from published financial report of the foreign go-public national banks form first quarter of 2010 until second quarter of 2014. Multiple regression analysis was used for analysis. It shows that LDR, LAR, IPR, NPL, APB, IRR, PDN, BOPO, and FBIR simulta-neously have significant effect on ROA. In addition, LAR and FBIR, PDN, BOPO, NPL, partially have positive significant effect on ROA. But, LDR, IPR and APB, and IRR partially have negative and insignificant effect on ROA.